Model Pembelajaran Colaborative Student Learning di Lingkungan Internet of Things - Sulindawaty; Vely Dora Meliani Purba; Melisa Van Breukelen (STMIK Budi Darma, 2022)
Indonesian education in the era internet of things has the impact of having to change the way schools learn. The learning process in schools located in different places, both inter-cities, regions and provinces certainly does not get a balanced experience. For example, the learning process and results of students in the regions and capitals certainly do not produce the same experience, such as the experience of obtaining teaching modules / learning materials, solving subject matter, discussion techniques, utilizing technology for the learning process and others. The Collaborative Student Learning (CSL) model is a new learning model that utilizes ICT. The CSL model is carried out by collaborating several schools in carrying out the teaching and learning process. CSL is one of the learning approaches by combining students from various schools from various regions, cities and provinces throughout Indonesia. The goal is to equalize the PBM process and improve the quality and quality of students. With this CSL model, students will get new learning experiences and can discuss inter-schools throughout Indonesia. The result of this research is the concept of Collaborative Student Learning model applied in the internet of things environment with an implementation mechanism consisting of orientation, exploration, sharing and collaboration, and conclusion steps. The application of this CSL model can provide a solution to encourage students to learn more actively, independently, according to their own learning rhythm which allows students to learn according to the latest developments.